INTERVENSI AROMA TERAPI DALAM PENINGKATAN KUALITAS TIDUR PASIEN DENGAN MASALAH KARDIOVASKULAR - Sucipto Dwitanta (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIKes Panti Waluya Malang, 2024)
Background: Poor sleep quality will lead to stressful conditions which can cause the release of epinephrine and norepinephrine thereby increasing the need for oxygen for the myocardium. Aromatherapy is recommended as a method without side effects, non-invasive, cheap and painless to reduce anxiety and improve sleep quality of cardiovascular patients. Purpose: The aim of this study is to analyze the potential of aromatherapy interventions in patients with cardiovascular disorders. Methods: The research method in this article uses a literature study approach. The articles will be selected based on the following criteria. The search sources in this article use scientific-based databases (ScienceDirect, PubMed, EBSCOhost, and Wiley Library Online). The search starts from December 2022 using the keywords Cardiac Patients – Aromatherapy – Sleep quality. Result: Inhalation aromatherapy with peppermint or lavender essential oil can improve the sleep quality of cardiovascular patients. Inhaling aromatic oil stimulates the sense of smell affecting the central nervous system. Lavender oil can reduce fatigue, anxiety, heart rate, respiratory rate, and blood pressure, improve lung and brain oxygenation, and improve sleep quality. The use of essential oils can be a safe and cost-effective therapy for sleep disorders and can reduce the overuse of prescription medications. Implication: Lavender and peppermint essential oils have a therapeutic effect that relaxes the body. These effects can make the body feel relaxed and release hormones that can help patients sleep. However, this intervention still needs further research specifically from the aspect of dose and medium of aromatherapy.